Diabetes Is Associated With Rapid Progression of Aortic Stenosis: A Single-Center Retrospective Cohort Study - Han, Kangning; Shi, Dongmei; Yang, Lixia; Xie, Meng; Zhong, Rongrong; Wang, Zhijian; Gao, Fei; Ma, Xiaoteng; Zhou, Yujie (Frontiers in Cardiovascular Medicine, 2022)
Background Mounting evidence indicates that rapid progression of aortic stenosis (AS) is significantly associated with poor prognosis. Whether diabetes accelerates the progression of AS remains controversial. Objectives The purpose of the present study was to investigate whether diabetes was associated with rapid progression of AS. Methods We retrospectively analyzed 276 AS patients who underwent transthoracic echocardiography at least twice with a maximum interval ≥ 180 days from January 2016 to June 2021. AS severity was defined by specific threshold values for peak aortic jet velocity (Vmax) and/or mean pressure gradient. An increase of Vmax ≥ 0.3 m/s/year was defined as rapid progression. The binary Logistic regression models were used to determine the association between diabetes and rapid progression of AS. Results At a median echocardiographic follow-up interval of 614 days, the annual increase of Vmax was 0.16 (0.00–0.41) m/s. Compared with those without rapid progression, patients with rapid progression were older and more likely to have diabetes (P = 0.040 and P = 0.010, respectively). In the univariate binary Logistic regression analysis, diabetes was associated with rapid progression of AS (OR = 2.02, P = 0.011). This association remained significant in the multivariate analysis based on model 2 and model 3 (OR = 1.93, P = 0.018; OR = 1.93, P = 0.022). After propensity score-matching according to Vmax, diabetes was also associated rapid progression of AS (OR = 2.57, P = 0.045). Conclusions Diabetes was strongly and independently associated with rapid progression of AS.